Detail specification for solder-sealed quartz crystal units for oscillator applications. AA, BF, CX and BC/1 enclosures, 0.8 to 20 MHz and 3.0 to 30 MHz frequency ranges. Fundamental thickness-shear mode, AT-cut, for operation over wide temperature ranges (non-temperature controlled). Full assessment level. (15th October 1977) - British Standards Institution,
No abstract available